IDL: A Geometric Interference Detection Language - Gamito, M. N.; Dias, J.; Pedro, S. (Atas do 10º Encontro Português de Computação Gráfica, 2001)
This paper describes a novel programming language approach to the problem of automatically verifying the design in an architectural and civil engineering project, fully described in 3D. The language is referred to as IDL, Interference Detection Language and is used to write geometric-based design verification tests, which are then interpreted and applied to an architectural 3D virtual scene, resulting in geometric interferences if the geometric objects of the scene fail to verify those tests. IDL operators are algorithmically based on simple Geometric Boolean Set and Constructive Solid Geometry operations are applied on a Binary Spatial Partitioning organisation of the 3D scene being analysed. This paper also presents Visual IDL, an intuitive graphical editor, which allows a common user to write design verification tests according to the IDL syntax notation and still be relatively independent of the language constructs. With Visual IDL, the user is not required to learn the language but can still write typical tests quickly and efficiently. Visual IDL can be considered a higher-level abstraction of the language, allowing the user to concentrate on what is required rather than how to execute it.